(untitled) (Archaeologia Adriatica, 2013)
The article analyzes a catalogue of 223 coins kept in the Classical Department of the Archaeological Museum in Zadar, for which it is known or presumed that they came from the area of Roman Zadar (Iader). On the basis of a section of these coins, whose provenience could be assumed with greater certainty and finds known from earlier publications, a sample was formed of 154 coins that served for the analysis of the intensity of coin circulation in the period between 294 and 455 AD in Zadar. The comparison of the curves of the intensity of the influx of coinage in Zadar with the sample covering the area of northern Dalmatia showed that Zadar deviated from the typical situation in northern Dalmatia. The most apparent differences refer to the maximal values of the circulation index, which for the Zadar sample shows a pattern of coins minted at intervals in 348-388, while the samples from northern Dalmatia show a pattern of coins minted at intervals in 330-341. After more detailed analysis, it is concluded that the circulation index of coins minted to 378 in both samples was similarly structured, while those minted later exhibit a considerable deviation. This was the year when the famous battle of Hadrianopolis took place.